DFS: Insuring customer service excellence through e-learning - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2017)
In early January 2017, Vanessa Teo, Director of Global Learning and Talent Development at the DFS Group, is outlining the airport retailer’s e-learning strategy. The Group had already invested significant resources in various training, learning and development programmes. These programmes, housed within DFS University, focused on building a deep knowledge and appreciation of the various luxury products sold by incoming sales associates. Associates in these programmes learn different types of sales tactics, and promising employees are enrolled in leadership programmes to fast-track their management potential. Nonetheless, these programmes were expensive. DFS first embarked on an e-learning initiative three years earlier with the development of an e-campus, which was a social learning platform akin to Facebook. This platform was piloted at many locations throughout DFSs’ worldwide network of airport duty free stores. The hope was that such social learning could simultaneously reinforce and scale up the learning and training development programmes. Now, Teo seeks to advance into the next stage of developing the e-learning initiative, envisioning a broader type of blended learning experience that could digitise some of DFS’s learning content into something even more scalable. However, e-learning at DFS is still a relatively new and untested tool. Teo needs to convince her counterparts to look past the development costs and embrace a more digital approach. In this case, students will analyse the pros and cons of e-learning as a training, learning and development tool in the service sector, such as retail. They will also discuss what aspects of training, learning and development are suitable for a digital format, and which are not. This case is suitable for subjects related to customer service, human resources and corporate learning.